2015
DOI: 10.1093/cercor/bhu317
|View full text |Cite
|
Sign up to set email alerts
|

Altered Functionality, Morphology, and Vesicular Glutamate Transporter Expression of Cortical Motor Neurons from a Presymptomatic Mouse Model of Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a lethal disorder characterized by the gradual degeneration of motor neurons in the cerebrospinal axis. Whether upper motor neuron hyperexcitability, which is a feature of ALS, provokes dysfunction of glutamate metabolism and degeneration of lower motor neurons via an anterograde process is undetermined. To examine whether early changes in upper motor neuron activity occur in association with glutamatergic alterations, we performed whole-cell patch-clamp recordings to ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 96 publications
5
91
0
Order By: Relevance
“…The reduced sSTD might also result from the change in presynaptic release probability that is determined by Ca 2+ level at synaptic terminals. In cortical mSOD1 G93A MNs, spontaneous excitatory postsynaptic currents were found to occur at higher frequency (Saba et al, 2016) due to over-expression of N-type VGCC (Pieri et al, 2013). Lautenschläger et al (Lautenschlager et al, 2013) reported a decelerated cytosolic Ca 2+ clearance due to disturbance of endoplasmic reticulum/mitochondria (ER/MT) in mSOD1 G93A MNs, which may enhance resting Ca 2+ .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced sSTD might also result from the change in presynaptic release probability that is determined by Ca 2+ level at synaptic terminals. In cortical mSOD1 G93A MNs, spontaneous excitatory postsynaptic currents were found to occur at higher frequency (Saba et al, 2016) due to over-expression of N-type VGCC (Pieri et al, 2013). Lautenschläger et al (Lautenschlager et al, 2013) reported a decelerated cytosolic Ca 2+ clearance due to disturbance of endoplasmic reticulum/mitochondria (ER/MT) in mSOD1 G93A MNs, which may enhance resting Ca 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular glutamate can be enhanced by the loss of glutamate transporters in glial cells, which has been found in both ALS patients (Rothstein et al, 1995) and mouse models (Bruijn et al, 1997; Bendotti et al, 2001). An increase in synaptic transmission was reported in hypoglossal MNs of neonatal mSOD1 G93A mice and in cortical MNs of young adult mSOD1 G93A mice (van Zundert et al, 2008; Saba et al, 2015). A disinhibitory synaptic mechanism may be involved in ALS due to breakdowns in glycinergic transmission (Chang and Martin, 2009; McGown et al, 2013) and the synaptic connections between MNs and Renshaw cells (Wootz et al, 2013).…”
Section: Introductionmentioning
confidence: 89%
“…Only protrusions with a clear connection of the head of the spine to the dendrite shaft were counted as spines; small processes were classified as a spine only if they were <3 µm long and <0.8 µm in cross- sectional diameter (Harris, 1999). Spine density was then expressed as the number of spines per 10 μm dendrite length (Saba et al, 2016; Jara et al, 2012; Vinsant et al, 2013). Number of mice N = 3 for both WT and SOD for each time point.…”
Section: Methodsmentioning
confidence: 99%
“…Of further relevance, morphologic and functional cortical neuronal changes, including apical dendritic regressions, loss of dendritic spines, and enhanced glutaminergic excitation, have been documented as either early or presymptomatic abnormalities in mouse models [134][135][136][137][138]. Importantly, these morphological and functional changes result in neuronal hyperexcitability.…”
Section: Pathogenic Implicationsmentioning
confidence: 99%